1991
DOI: 10.1172/jci115086
|View full text |Cite
|
Sign up to set email alerts
|

Long-term antidepressant administration alters corticotropin-releasing hormone, tyrosine hydroxylase, and mineralocorticoid receptor gene expression in rat brain. Therapeutic implications.

Abstract: Imipramine is the prototypic tricyclic antidepressant utilized in the treatment of major depression and exerts its therapeutic efficacy only after prolonged administration. We report a study of the effects of short-term (2 wk) and long-term (8 wk) administration of imipramine on the expression of central nervous system genes among those thought to be dysregulated in imipramine-responsive major depression. As assessed by in situ hybridization, 8 wk of daily imipramine treatment (5 mg/kg, i.p.) in rats decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
142
4
1

Year Published

1994
1994
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 326 publications
(165 citation statements)
references
References 27 publications
18
142
4
1
Order By: Relevance
“…Comparable to imipramine, the SJW extract and hypericin reduced plasma ACTH and corticosterone levels after 2 weeks of daily treatment. In line with previous findings (Brady et al, 1991;Nestler et al, 1990), we found that long-term treatment with imipramine significantly decreased TH mRNA levels in the locus coeruleus, whereas SJW extract and hypericin had no effect on TH message levels. Furthermore, long-term treatment with all three agents significantly decreased 5-HT 1A receptor mRNA expression in CA1 of the hippocampus.…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…Comparable to imipramine, the SJW extract and hypericin reduced plasma ACTH and corticosterone levels after 2 weeks of daily treatment. In line with previous findings (Brady et al, 1991;Nestler et al, 1990), we found that long-term treatment with imipramine significantly decreased TH mRNA levels in the locus coeruleus, whereas SJW extract and hypericin had no effect on TH message levels. Furthermore, long-term treatment with all three agents significantly decreased 5-HT 1A receptor mRNA expression in CA1 of the hippocampus.…”
Section: Introductionsupporting
confidence: 92%
“…In an animal study designed to examine the association between long-term antidepressant administration and the possibly delayed alteration in HPA axis activity, CRH mRNA levels in the hypothalamic paraventricular nucleus (PVN) of rats were shown to be decreased following longterm (8 weeks) but not short-term (2 weeks) treatment with imipramine, the prototypic tricyclic antidepressant (Brady et al, 1991). The same results were found with several other antidepressant drugs selected for their distinctly different primary pharmacological actions (Brady et al, 1992).…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Another system that is markedly altered following chronic antidepressant treatment is the HPA axis. For example, following long (8 weeks), but not short (2 weeks) treatment with either fluoxetine or imipramine, CRH mRNA was decreased by 30-48% in the hypothalamic PVN (Brady et al 1991(Brady et al , 1992. Moreover, chronic treatment with fluoxetine, as well as other antidepressants, significantly elevated the levels of glucocorticoid receptors in the hippocampus (Brady et al 1991(Brady et al , 1992, which normally mediate the negative feedback response to stress-induced activation of the HPA axis (Sapolsky et al 1984).…”
Section: Discussionmentioning
confidence: 99%
“…For example, following long (8 weeks), but not short (2 weeks) treatment with either fluoxetine or imipramine, CRH mRNA was decreased by 30-48% in the hypothalamic PVN (Brady et al 1991(Brady et al , 1992. Moreover, chronic treatment with fluoxetine, as well as other antidepressants, significantly elevated the levels of glucocorticoid receptors in the hippocampus (Brady et al 1991(Brady et al , 1992, which normally mediate the negative feedback response to stress-induced activation of the HPA axis (Sapolsky et al 1984). Finally, our results are in agreement with previous studies in experimental animals (Reul et al 1993) and in healthy humans (Michelson et al 1997), which reported that chronic treatment with antidepressants markedly attenuated the pituitary-adrenal response to stressful or pharmacological challenges.…”
Section: Discussionmentioning
confidence: 99%